Effect of tobacco and nicotine in causing staining of dental hard tissues and dental materials: A systematic review and meta‐analysis. Issue 1 (13th November 2022) - Karanjkar, Rijula R.; Preshaw, Philip M.; Ellis, Janice S.; Holliday, Richard
Abstract: Introduction: Dental staining is a common concern for tobacco users. However, little is known about which components of tobacco are responsible for the staining and whether nicotine may be implicated. This is of increasing relevance with the popularity of novel products such as heated‐tobacco products and electronic cigarettes (E‐cigarettes). Objectives: This systematic review aimed to establish the evidence base for the effect if any, of the various tobacco and nicotine products in causing staining of dental hard tissues and materials. Material and Methods: This systematic review was performed in accordance with the preferred reporting items for systematic reviews and meta‐analyses guidelines. There were four structured population intervention comparison outcomesquestions. A search was conducted up to December 2021 in three databases: MEDLINE, EMBASE,  and Web of Science, and manual searching of relevant sources was also completed. Two researchers individually reviewed the titles then abstracts and finally full articles. A reporting quality appraisal was conducted appropriately to the study methodology. Results: Of the 815 records titles identified, 56 full‐text articles were assessed for eligibility, of which 27 were included for analysis. The included studies were mainly laboratory studies of varying reporting quality. There was evidence from 18 studies that tobacco exposure caused staining of dental hard tissues (pooled results from three studies‐ enamel/dentine; mean difference [MD]: 16.22; 95% confidence interval[12.11, 20.32; I 2 : 96%)and materials (pooled result from four studies—resin composite; MD: 11.90; 95% CI: 11.47, 12.34; I 2 : 100%). There was limited evidence that E‐cigarettes 99%) and heated tobacco products (HTPs; pooled results from three studies–−1.07, 6.54; I 2 : 99%) cause staining, but this was lower than with traditional tobacco/found 11 compounds, of which 8 were terpenoids, from tobacco products implicated in causing staining. Finally, there was some evidence that resin composites stained more than other materials. Conclusions: Tobacco smoking causes dental staining. There was limited evidence that E‐cigarettes and HTPs did cause dental staining that was less intense than that caused by traditional tobacco products.